Oribatid mites (Acari, Oribatida) in Soils of the Russian Far East - Ryabinin, Nikolay A. (Zootaxa, 2015)
The present paper reviews the taxonomic studies of the mite suborder Oribatida in the Russian Far East and gives a checklist of 596 species and subspecies in 228 genera, representing 84 families. The checklist includes data from more than 230 habitats of the Russian Far East from Chukotka to the Southern Primorye. In addition, a short historical and biogeographical review of oribatid mites study in the Russian Far East is presented.